Dream jumper. Book one, Nightmare escape - Grunberg, Greg (Graphix, 2016)
Ben has the gift of being able to jump into other people's dreams--an ability that comes in handy when his classmates start experiencing the same evil dream monster. He will need the help of a mysterious companion to save all his friends in time.